The woods ; Lakeboat ; Edmond : - Mamet, David (Grove Press, 1987)
Three plays by David Mamet: The Woods, Lakeboat, and Edmond. The Woods, described by the Chicago Daily News as a 'beautifully conceived love story; Lakeboat, eight crew members aboard a merchant ship exchange their wild fantasies about sex, gambling, and violence; Edmond, a man set morally adrift leaves an unfulfilling marriage to find sex, adventure, companionship, and, ultimately, the meaning of his existence.